1988
DOI: 10.1177/0148607188012004332
|View full text |Cite
|
Sign up to set email alerts
|

Branched‐Chain Amino Acids Metabolic Support in Surgical Patients: A Randomized, Controlled Trial in Patients with Subtotal or Total Gastrectomy in 16 Japanese Institutions

Abstract: A prospective, randomized, controlled trial of nutritional effects of branched-chain-enriched amino acid (BCAA) solution was undertaken in 173 surgical patients with gastric cancer. Eighty-six and 87 patients underwent subtotal and total gastrectomy, respectively. The effects were evaluated in total parenteral nutrition (TPN) in an isocaloric/isonitrogenous setting where the major difference between the group was the amount of BCAA received. Each 80 patients in the control and the BCAA groups completed the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…amino acids themselves, and various physiological functions, such as antioxidative action, are exhibited through absorption into the body. 23,24) Based on the above information, caffeic acid derivatives and polyphenols that capture · OOH, · OH and · O 2 Ϫ as radical scavengers, and b-sitosterol, which exerts a preventive action by inhibiting the excess production of active oxygen by various cells, may be involved in the antioxidative action of ESE in a complex manner.…”
Section: Discussionmentioning
confidence: 99%
“…amino acids themselves, and various physiological functions, such as antioxidative action, are exhibited through absorption into the body. 23,24) Based on the above information, caffeic acid derivatives and polyphenols that capture · OOH, · OH and · O 2 Ϫ as radical scavengers, and b-sitosterol, which exerts a preventive action by inhibiting the excess production of active oxygen by various cells, may be involved in the antioxidative action of ESE in a complex manner.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this premise, numerous projects studying the effect of BCAA in the critically ill have been published [1][2][3][4][5][6][7][11][12][13][14][15][16][17]. A majority of these studies have used nitrogen balance as their gold standard in terms of evaluating the benefit of BCAA.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of these studies have used nitrogen balance as their gold standard in terms of evaluating the benefit of BCAA. With this as a criterion, several studies have shown a positive effect for BCAA in critically ill patients [1][2][3][4][5][6][7], while others have shown no beneficial effects [11][12][13][14][15][16][17]. It is worth noting that in none of these studies were detrimental effects of BCAA documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…95 High BCAA-enriched TPN has been widely used in postoperative and critically ill patients, and has usually shown an improvement of amino acid utilization and nitrogen balance, as well as protein metabolism. 98,99 Although TPN supplemented with specific nutrients has also been shown to improve the nutritional status in patients with noncancerous diseases, the effects of these specific nutrients in patients with cancer should be carefully evaluated, since it is possible that the administration of these specific nutrients, which are beneficial to the host, might also be beneficial for tumor growth. Although some animal studies have shown that the continuous administration of BCAA to tumor-bearing rats caused a significant increased in survival time and a significant reduction in tumor size, 100 no substantial data in human patients with cancer have been provided regarding the metabolism of the host and tumor.…”
Section: Supplementation Of Specific Nutrients and The Response Of Thmentioning
confidence: 99%